ANALISIS PENGARUH RISIKO KREDIT TERHADAP PROFITABILITAS (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017) - Prasiska Widya Kumaralita; Agus Purwanto (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to know how the effect of credit risk on the profitability of banking companies in Indonesia. This research uses Non Performing Loan (NPLR), Loan Loss Provision Ratio (LLPR), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and Cost per Loan Asset (CLA) as indicators of credit risk. The performance of a good banking company can be reflected in all the financial information provided by the banking company regarding the profitability of the company.The type of data used in this study is secondary data and use the population of banking companies go public listed on the Indonesia Stock Exchange (IDX) in the period 2014-2017. The sample selection method in this study used purposive sampling technique with the criteria of banking companies that consistently publish financial statements and provide data such as Return on Asset (ROA), Return on Equity (ROE), Non Performing Loan (NPLR), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and other data required and presented in rupiah currency in the period 2014-2017. The study use multiple linear regression analysis method for hypothesis testing.The results showed that there was a significant negative or positive correlation between credit risk indicator and banking company profitability measured by Return on Asset (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). But the impact of all of the above explanatory variables varies and differs. It can be concluded that low levels of Non Performing Loans (NPLRs), and low Cost Per Loan Assets (CLAs) will result in high levels of bank profitability, while high Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) levels describes the high level of banking profitability. While Loan Loss Provision Ratio (LLPR) does not have a significant influence on the profitability of banking companies.